Challenges and opportunities in the operationalization of the Water-Environment-Energy-Food (WE2F) Nexus: Case study of the upper Niger basin and inner Niger delta, West Africa - Seidou, O.; Maiga, F.; Ringler, Claudia; Kalcic, S.; Ferrini, L. (EDP Sciences, 2020)
The ever-increasing demand for water, food, and energy is putting unsustainable pressure on natural resources worldwide, often leading to environmental degradation that, in turn, affect water, food, and energy security. The recognition of the complex interlinkages between multiple sectors has led to the creation of various holistic approaches to environmental decision making such as Integrated Natural Resources Management (INRM), Integrated Water Resources Management (IWRM), Virtual Water (VW), Water Footprint (WF) and lately the Food-EnergyEnvironment-Water nexus (WE2F). All these approaches aim to increase resource use efficiency and promote sustainability by increasing the cooperation between traditionally disjoint sectors, and mainly differ by the number and relative weights of the sectors included in their framework. They also suffer from the same face and the same barriers for implementation, some of which may never be fully overcome. The paper discusses the benefits of adopting a WE2F nexus approach in the Upper Niger Basin (UNB) and the Inner Niger Delta (IND), but also the multiple difficulties associated with its practical implementation. IWRM/WE2F initiatives in the UNB/IND such as the BAMGIRE project piloted by Wetlands International and funded by the Dutch Embassy in Mali to secure livelihoods and biodiversity in a changing environment, is taken as an example of partial success in the use of a nexus approach to watershed management. It was shown there are multiple barriers to the operational implementation of the WE2F. However, while a full understanding of all interlinkage between sectors may never be possible, data collection, scientific research and model development can improve our ability to understand the complex system in which we live, and hence take better decisions